Relationship between selected perinatal paratuberculosis management interventions and passive transfer of immunity in dairy calves. (9th July 2016) - McAloon, C. G.; Whyte, P.; O'Grady, L.; Lorenz, I.; Green, M. G.; Hogan, I.; Johnson, A.; Doherty, M. L.
Abstract : The objective of this cohort study was to assess the relationship between perinatal calf management practices relevant to the control of paratuberculosis and passive transfer of immunoglobulin in calves born in an endemically infected Irish dairy herd. Data from 176 calves were used to assess the effect of time spent in the calving area, individual versus non‐designated calving and colostrum pasteurisation on serum total protein, zinc sulphate turbidity, globulin and γ‐glutamyltransferase. In addition, the effects of colostrum quality, volume of colostrum fed, method of colostrum administration and calving season on passive transfer were quantified. Serum samples were collected as part of routine herd health monitoring from calves aged between one and seven days. Multivariate linear and logistic regression models were used to assess the effect of each variable on the test result and failure of passive transfer as determined using a cut‐off point for each diagnostic test. Colostrum pasteurisation and calving area were not significantly associated with passive transfer, whereas increased time spent in the calving pen was consistently associated with a detrimental effect. In addition, a strong seasonal effect was apparent, which appeared to be unrelated to colostrum quality and calf management. The authors are unaware of published studies documenting such a significant seasonal effect on passive transfer.